Is rivaroxaban associated with lower inpatient costs compared to warfarin among patients with non-valvular atrial fibrillation?. (August 2014) - Laliberté, François; Pilon, Dominic; Raut, Monika K.; Nelson, Winnie W.; Olson, William H.; Germain, Guillaume; Schein, Jeff R.; Lefebvre, Patrick
Abstract Background: Warfarin has been the mainstay treatment used by patients with a moderate-to-high risk of stroke due to non-valvular atrial fibrillation (NVAF). Unlike rivaroxaban, laboratory monitoring to allow the attainment of the prothrombin time international normalized ratio goal is required with warfarin, thereby potentially increasing a patient's hospitalization costs. Objective: To compare hospitalization costs between hospitalized NVAF patients using rivaroxaban versus warfarin in a real-world setting. Methods: A retrospective claims analysis was conducted using the Premier Perspective Comparative Hospital Database from November 2010 to September 2012. The study included adult patients hospitalized for NVAF after November 2011. Patients using rivaroxaban during hospitalization were matched with up to four warfarin users by propensity score analyses. Hospitalization costs were compared between the matched cohorts using generalized estimating equations. A sub-analysis was performed for patients who were first administered their treatment on day three or later of their hospital stay. Sensitivity analyses were conducted on matched cohorts with a primary diagnosis of AF. Results: The matched cohorts' (2809 rivaroxaban and 11, 085 warfarin users) characteristics were well balanced. The mean age of cohorts was 71 years and 49% of patients were female. The average hospitalization cost of rivaroxaban users was $11, 993 compared to $13, 255 for warfarin users. The cost difference was significantly lower by $1284 (P < 0.001). Patients who were administered rivaroxaban treatment on day three or after incurred significantly lower hospitalization costs (cost difference: $4350; P < 0.001) compared to warfarin users. Rivaroxaban users with a primary diagnosis of AF also had significantly lower costs compared to warfarin users. Limitations: These included possible inaccuracies or omissions in diagnoses, completeness of baseline characteristics, and a study population that included patients newly initiated on and patients who continued anticoagulant therapy. Conclusion: Hospitalization costs for rivaroxaban were significantly lower than those for warfarin in NVAF patients treated with rivaroxaban.